TEMPERATURE-DEPENDENCE OF CONFORMATIONAL PROPERTIES OF SHORT POLYELECTROLYTES FROM SIMULATIONS AT A SINGLE TEMPERATURE - Chahine, J.; Guimaraes, M. A.; Cavichiolli, F. R. (Amer Chemical Soc, 1994)
We use a series expansion method introduced recently by Rickman and Phillpot (Phys. Rev. Lett. 1991, 66, 349) to study the temperature dependent conformational properties of short ionized polyelectrolyte chains in ionic solutions by conducting simulations at a single temperature. The charged beads located at the sites of a cubic lattice interact through screened Coulombic interactions. It is shown that this method provides results that correlate with other Monte Carlo simulations, performed over a range of temperatures, where conformational transitions induced by thermal and screening effects occur. It is also shown that the method can be used successfully when the potential is weakly dependent on temperature.